The Impact of Climate Change on Public Health: a Case Study of the Increase in Tropical Diseases in Southeast Asia - Fitri Nurhayati; Hajar (CV. Get Press Indonesia, 2025)
Climate change increasingly threatens human health, especially in tropical regions like Southeast Asia. This study analyzes the relationship between climate change and the dynamics of tropical diseases in the region to provide evidence-based recommendations for public health policy and climate adaptation. Using a quantitative approach, the research employs a time-series ecological study design and spatial analysis to examine associations between climate variables such as temperature, rainfall, and humidity and the incidence of tropical diseases like dengue hemorrhagic fever (DHF) and cholera from 2010 to 2024. Statistical analyses were conducted using Distributed Lag Non-Linear Models (DLNM), while Geographic Information Systems (GIS) identified spatial clusters with high disease risk. The results demonstrate that climate variability significantly increases disease burden, with extreme weather events creating favorable conditions for the spread of climate-sensitive diseases. These findings strengthen vector-ecological theory and the framework of environmentally mediated pathogens, emphasizing the role of climatic conditions in disease patterns. A key novelty of this study is its integration of both temporal and spatial modeling to assess localized disease risk, enabling more precise identification of vulnerable areas. This integrated approach provides actionable insights to enhance early warning systems, improve environmental sanitation, and develop local adaptation strategies. Ultimately, the study underscores the urgent need for climate-informed health planning in Southeast Asia to reduce the public health impacts of ongoing climate change.